Presentation of CS-MAP Results in the municipalities of Canaman and Pamplona, Camarines Sur - Gutierrez, Mary Anne; Raviz, Jeny; Garcia, Cornelia; Castillo, Rowena (International Rice Research Institute, 2023)
Canaman and Pamplona are municipalities in Camarines Sur, a province in the Bicol region frequently affected by extreme weather events, particularly typhoons. These areas are also rice-producing regions, where farming is a primary livelihood. To address these challenges, the CGIAR Research Initiative on Climate Resilience (ClimBeR) has implemented the Climate-Smart Mapping and Adaptation Planning (CS-MAP), a participatory mapping approach developed by CCAFS-SEA. CS-MAP is designed to assess climate-related risks, map vulnerable areas, and develop location-specific adaptation plans. This presentation shared preliminary findings with partners and stakeholders in Camarines Sur, including climate risk maps and consolidated adaptation plans, to gather further input for consultation and validation.